2019
DOI: 10.1016/j.jad.2019.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent fluoxetine history impairs spatial memory in adult male, but not female, C57BL/6 mice

Abstract: Background: Epidemiological reports indicate that mood-related disorders are common in the adolescent population. The prevalence of juvenile major depressive disorder has resulted in a parallel increase in the prescription rates of fluoxetine (FLX) within this age group. Although such treatment can last for years, little is known about the enduring consequences of adolescent antidepressant exposure on memory-related performance. Methods:We exposed separate groups of adolescent (postnatal day [PD] 35) male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…This would be in agreement with recent findings illustrating that fluoxetine hinders neurogenesis after 6 and 9, but not after 3 weeks of intake (Ohira, Hagihara, Miwa, Nakamura, & Miyakawa, 2019). Still, the length of the applied treatment may not be an exclusive explanation of the discrepancies in the literature, as deteriorating effects of fluoxetine have been reported after chronic drug administration significantly shorter than the one used in the present research (Dringenberg, Branfield Day, & Choi, 2014;Eisenreich, Greene, & Szalda-Petree, 2017;Flores-Ramirez et al, 2019;Frick, Bernardez-Vidal, Hocht, Zanutto, & Rapanelli, 2015;Sharp et al, 2019;Takahashi et al, 2005). In addition, as our experiments were performed in an inbred strain from a local colony, it may be that the reported effects occur only against this specific genetic background.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This would be in agreement with recent findings illustrating that fluoxetine hinders neurogenesis after 6 and 9, but not after 3 weeks of intake (Ohira, Hagihara, Miwa, Nakamura, & Miyakawa, 2019). Still, the length of the applied treatment may not be an exclusive explanation of the discrepancies in the literature, as deteriorating effects of fluoxetine have been reported after chronic drug administration significantly shorter than the one used in the present research (Dringenberg, Branfield Day, & Choi, 2014;Eisenreich, Greene, & Szalda-Petree, 2017;Flores-Ramirez et al, 2019;Frick, Bernardez-Vidal, Hocht, Zanutto, & Rapanelli, 2015;Sharp et al, 2019;Takahashi et al, 2005). In addition, as our experiments were performed in an inbred strain from a local colony, it may be that the reported effects occur only against this specific genetic background.…”
Section: Resultssupporting
confidence: 93%
“…Regrettably, studies describing the influence of fluoxetine on cognitive and emotional well‐being in such individuals are still rare(Olguner Eker, Özsoy, Eker, & Doğan, 2017; Serretti et al, 2010). However, there is increasing evidence in both healthy animals and human subjects that the drug hinders reward processing (Eisenreich, Greene, & Szalda‐Petree, 2017; Flores‐Ramirez et al, 2019; Sharp et al, 2019) and can suppress neuronal plasticity (Dringenberg, Branfield Day, & Choi, 2014). In particular, it has been reported that chronic fluoxetine treatment decreases amygdala activation in healthy adults (Takahashi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The heated pool (22°C; 150 cm diameter) was divided into 4 quadrants with a designated visual cue in each quadrant ( Figure 3G ). We used a 4-day protocol ( Flores-Ramirez et al, 2019 ) starting with a pre-training/habituation day where the location of the escape platform was introduced with the platform being visible 1 cm above the water surface. Each animal was placed on the platform for 10 s before being released into the water facing the platform, less than 10 cm away.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, memory recall on probe trial showed a significant effect of fluoxetine treatment on time spent in target quadrant (dwell time): t (14) = 11.443, p = 0.0005 (Figure e). Similarly, a previous study had reported that fluoxetine treatment for 15 days impairs spatial memory recall of nonstressed mice on Morris water maze, but does not impair acquisition learning or novel object recognition . Since no confounds were found in the memory assessments, animals were rehabilitated and no further estimations were made on LD + Flx group.…”
Section: Resultsmentioning
confidence: 90%